Aging engineers’ occupational self-efficacy—a mixed methods study - Wallin, Stina; Fjellman-Wiklund, Anncristine; Fagerström, Lisbeth (Frontiers in Psychology, 2023)
Introduction Engineers’ work has become more complex with increased demands in today’s changing working life. Self-efficacy is essential to successfully adapt to work-related changes and to cope with adverse job demands. However, less is known about aging engineers’ occupational self-efficacy. Therefore, this study explores facilitators and barriers to aging engineers’ occupational self-efficacy beliefs to continue working until expected retirement age. An additional purpose is to explore if any of the aspects described by the engineers are more prominent. Methods The study design was exploratory, using mixed methods with a qualitative to quantitative approach. A total of 125 engineers, aged between 45 and 65 years, answered two open-ended survey questions about what positively and negatively affect their occupational self-efficacy beliefs to continue working. First, data was analyzed using an inductive manifest qualitative content analysis. Next, descriptive statistics were performed based on the results of the qualitative study. Results The analyses revealed that health and working conditions that affect health were crucial facilitators and barriers for the aging engineers’ occupational self-efficacy to continue working until expected retirement age. Furthermore, the engineers emphasized competence, motivation from meaningful tasks, family and leisure, and private economy. Discussion The aging engineers’ own health seems to be prominent in their self-efficacy regarding a full working life; consequently, support still needs to address issues affecting health.